2008
DOI: 10.1007/s10508-008-9356-7
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Down Low: Sexual Risk, Protection, and Disclosure Among At-Risk Black Men Who Have Sex with Both Men and Women (MSMW)

Abstract: Little information is available about sexual risk, protective, and disclosure practices among Black bisexually active men and how these may be amenable to intervention when necessary. In-depth interviews were conducted with 30 at-risk urban Black men who have sex with both men and women (MSMW). Participants reported protecting themselves and their partners through routine HIV testing, using condoms consistently, engaging in strategic positioning during sexual activity, and limiting the number of sexual partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 36 publications
9
132
1
1
Order By: Relevance
“…Sexual minorities experience disparities in social support and connectedness, mediating the development of harmful psychosocial outcomes (Coulter, Herrick, Friedman, & Stall, 2016;Frost, Meyer, & Schwartz, 2016). However, cultivating sources of social support may be particularly difficult for some black MSMW, who often face ongoing marginalization from familial and religious institutions into adulthood (Dodge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual minorities experience disparities in social support and connectedness, mediating the development of harmful psychosocial outcomes (Coulter, Herrick, Friedman, & Stall, 2016;Frost, Meyer, & Schwartz, 2016). However, cultivating sources of social support may be particularly difficult for some black MSMW, who often face ongoing marginalization from familial and religious institutions into adulthood (Dodge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Black MSMW may also be more likely than MSM of other race/ethnicities to have undiagnosed infection (Maulsby, Sifakis, German, Flynn, & Holtgrave, 2012;Young, Shoptaw, 5 It is likely that sexual behaviors differ between male, female, and transgender partners of MSMW . Some research suggests that MSMW practice more unprotected sex with their female partners than with their male partners (Dodge, Jeffries, & Sandfort, 2008;Mimiaga et al, 2009) and with primary partners compared to non-primary partners (Sanchez et al, 2006;Sullivan, Salazar, Buchbinder, & Sanchez, 2009). Harawa et al noted that Black MSMW who had only primary female partners had fewer male partners and were also more likely to have only primary partners .…”
mentioning
confidence: 99%
“…[3][4][5][6] The considerable research on male same-sex behavior typically focuses on men who have sex with men only (MSM) and does not treat MSMW as a distinct subpopulation. 7 A survey of about 10,000 men who have sex with men conducted in 2003-2005 by the Centers for Disease Control and Prevention in 17 US metropolitan areas found that 14% also reported having sex with women in the previous 12 months. 8 While this study did not report on racial/ethnic differences in male bisexuality, a review of 26 studies by Millet and colleagues 5 concluded that among MSM in the USA, bisexual behavior is more prevalent among blacks than whites and Latinos.…”
Section: Introductionmentioning
confidence: 99%
“…Behaviorally, MSMW are not a monolithic group, as some have sex more often with women, others with men, and others equally with women and men. 7,31 Some studies suggest that bisexual men who experience greater dissonance between their behavior and orientation or who are more secretive about their male sexual relationships engage in greater risk, including having more sex partners and unprotected sex and using condoms less consistently 32 while other studies report less risk. 33 Sexual self-identification is also important for accessing MSMW for interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Sementara itu, studi lain menyebutkan rerata jumlah pasangan seks seumur hidup yang dapat dimiliki individu sejumlah 10 orang (Dodge, Jeffries IV, & Sandfort, 2008).…”
Section: Jumlah Pasangan Seksunclassified